Evaluation of Nonlinear Growth Curve Models in Native Crossbred Chickens - Sopian, Yusup; Latifah, Latifah (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2024)
Mathematical models in poultry development programs can provide valuable information. The present study aimed to determine an appropriate non-linear growth model in native crossbred chickens (NCC). The data used in this study were from published article reporting body weight report of native crossbred chickens from natural mating between the male Sentul (SC) breed and the female Kampung chicken breed (KC). The NCC body weight (BW) was recorded weekly from 1 to 12 weeks. Three non-linear growth curve models (Gompertz, Logistic, and Weibull) were used to model NCC growth performances. The best-fit model was measured with a coefficient of determination (R2), adjusted coefficient of determination (AdjR2), and root mean square error (RMSE). The results showed that Gompertz models (R2: 0.97, 0.96; AdjR2: 0.97, 0.96; RMSE: 18.89, 13.63 for males and females, respectively) were more favorable. Age at inflection ranged from 9.29 to 11.30 weeks for males and 9.12 to 11.13 weeks for females, respectively. Estimated weights at inflection ranged from 686.13 g to 920.40 g for males and 553.46 to 742.09 g for females. In conclusion, the Gompertz model is the most suitable model for describing the growth curve of native crossbred chickens.